2015
DOI: 10.7454/efi.v61i2.507
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Stock Market Integration Pre-Post Subprime Mortgage Crisis: Insight From BRIC Countries

Abstract: This study revisits the long-run relationships and short-run dynamic causal linkages among BRIC stock market, with the particular attention to the 2008 subprime mortgage crisis. Extending related empirical studies, comparative analyses of pre-crisis, and post-crisis periods were conducted to comprehensively evaluate how stock market integration was affected by financial crises. In general, after employing cointegration test and VAR test, the results reveal the increase of stock market integration in BRICs afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…In this context, Lehkonen (2015) observes that the global financial crisis had increased the degree of stock market integration in emerging market economies and reduced it in developed economies. Some studies found an increase in the degree of stock market integration in BRICS region during and after the financial crises (Ahmad et al, 2013; Fahami, 2011; Gupta, 2011; Puah et al, 2015; Singh & Kaur, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, Lehkonen (2015) observes that the global financial crisis had increased the degree of stock market integration in emerging market economies and reduced it in developed economies. Some studies found an increase in the degree of stock market integration in BRICS region during and after the financial crises (Ahmad et al, 2013; Fahami, 2011; Gupta, 2011; Puah et al, 2015; Singh & Kaur, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[14] stated that oil-exporting countries were positively associated with the stock market, whereas the adverse impact occurred in oilimporting countries. Other key determinants such as gold [15][16], GDP [17][18], exchange rate [16,[18][19], and economic crises [10,[20][21][22] were employed in previous studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the research Puah et al (2015) has been revisits the long-run relationships and short-run dynamic causal linkages among BRIC stock market, with the particular attention to the 2008 subprime mortgage crisis. The evidence also found that China stock market is the most influential among the BRICs, in which China stock market has the ability to Granger cause the other three BRICs member countries.…”
Section: Previous Research and Hypothesis Developmentmentioning
confidence: 99%